2010
DOI: 10.1016/j.ajhg.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-Recessive Hypophosphatemic Rickets Is Associated with an Inactivation Mutation in the ENPP1 Gene

Abstract: Human disorders of phosphate (Pi) handling and hypophosphatemic rickets have been shown to result from mutations in PHEX, FGF23, and DMP1, presenting as X-linked recessive, autosomal-dominant, and autosomal-recessive patterns, respectively. We present the identification of an inactivating mutation in the ecto-nucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) gene causing autosomal-recessive hypophosphatemic rickets (ARHR) with phosphaturia by positional cloning. ENPP1 generates inorganic pyrophosphate (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(180 citation statements)
references
References 23 publications
3
176
0
1
Order By: Relevance
“…These biochemical findings excluded rickets from nutritional deficiencies, and rapidly corrected when dairy product consumption decreased. Some GACI patients develop hypophosphatemic rickets, (18,25,70) perhaps related to the disturbance of PPi metabolism. (71) Acquired hypophosphatemia and rickets (OMIM# 613312) caused by his two altered ENPP1 alleles was an unlikely cause of his bone problems because his serum Pi level fell below the normal range just once as we followed him and without hyperphosphaturia.…”
Section: Discussionmentioning
confidence: 99%
“…These biochemical findings excluded rickets from nutritional deficiencies, and rapidly corrected when dairy product consumption decreased. Some GACI patients develop hypophosphatemic rickets, (18,25,70) perhaps related to the disturbance of PPi metabolism. (71) Acquired hypophosphatemia and rickets (OMIM# 613312) caused by his two altered ENPP1 alleles was an unlikely cause of his bone problems because his serum Pi level fell below the normal range just once as we followed him and without hyperphosphaturia.…”
Section: Discussionmentioning
confidence: 99%
“…5 A and B). Among these, the R456Q, L579F, L611V, C726R, N792S, E893X, and Y901S mutations abolished the enzymatic activity in human Enpp1 (5,32). The structure of mouse Enpp1 revealed that most of these residues participate in intradomain or interdomain interactions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 2006, a mutation in the gene encoding for the dentin matrix protein (DMP1; MIM 600980) was identified in patients with autosomal recessive HR (ARHR1; MIM 241520), 6 and a mutation in ectonucleotide pyrophosphatase/ phosphodiesterase 1 (ENPP1; MIM 173335) was in 2010 shown to cause autosomal recessive HR (ARHR2; MIM 613312). 7,8 XLHR, ADHR, ARHR1 and ARHR2 share identical biochemical characteristics of excessive renal phosphate wasting and low-serum phosphate associated with elevated levels of serum FGF23 and accompanied by inappropriately low serum 1,25-dihydroxyvitamin D (1,25(OH) 2 D). 8,9 Two types of HR differ biochemically from the four described types, as they are characterised by hypercalciuria: Hereditary HR with hypercalciuria (HHRH; MIM 241530), where the hypercalciuria is due to increased serum 1,25(OH) 2 D. The inheritance is autosomal recessive and the disease is caused by a mutation in the sodium-cotransporter gene (SLC34A3; MIM 609826), identified in 2006.…”
Section: Introductionmentioning
confidence: 99%